Enhancing creative competence of preservice teachers through pedagogical strategies in fashion design education - Amegbanu, Vida Adzo; Mpuangnan, Kofi N; Govender, Samantha; Ondigi, Samson Rosana; Oigo, Elizabeth Bosibori (Edelweiss Applied Science and Technology, 2025)
This study investigated how to enhance creative competence of preservice teachers through pedagogical strategies in fashion design education. A descriptive survey design was adopted, utilizing a stratified sampling technique to gather data from a total of 188 respondents. The respondents include 165 students, 18 tutors, and 5 principals. The data were collected through a structured questionnaire featuring close-ended questions. The analysis incorporated both descriptive and inferential statistical methods, including frequency percentages, means, standard deviations, and chi-square tests, with a significance level set at p < 0.05. The findings revealed that both teacher-related and student-related factors significantly contribute to fostering innovative teaching and learning in the context of fashion design. Pedagogical approaches such as project-based inquiry, experimentation, and the integration of internet resources were identified as particularly effective in enhancing creativity within fashion design education. To further promote student creativity, the study recommends the increased implementation of Technology-Enhanced Learning (TEL) environments and the adoption of strategies such as computer-aided design and outsourcing. Moreover, the study advocates for educational institutions to establish training programs aimed at equipping instructors with the necessary skills to effectively integrate Information and Communication Technology (ICT) into fashion design instruction, thereby advancing creativity in specialized fields.